Foot self-care practices reported by people with type 2 diabetes mellitus from a qualitative approach - Miranda-Torres, Lesly Patricia (2025)
Introduction: The appearance of diabetic foot is common but preventable. Self-care is a strategy to achieve this. Objective: To know the foot self-care practices reported by people with type 2 diabetes mellitus from a qualitative approach. Methods: Qualitative descriptive study. 12 people participated, selected by thematic saturation and redundancy and convenience sampling. Data collection was carried out between April and May 2023, through a semi-structured interview. Data processing was through thematic content analysis. Results: No glycosylated hemoglobin was found in the medical records and the center does not have a diabetic foot unit. In the analysis, four categories were found: a) Habits in examination, hygiene, nail trimming, drying and moisturizing the feet, b) Choice of footwear, c) Use of traditional medicine, d) Self-learning and need for education sanitary for self-care of the feet. Patients reported inspecting, washing, and drying their feet; Some do not hydrate them, do not cut their nails properly, walk barefoot, and prefer to use home-made therapeutic alternatives instead of going to the health center. They receive partial support from their family and limited education from health personnel for self-care. Conclusions: There are some adequate and other deficient practices in relation to foot self-care, limitations in educational aspects by health personnel, resource limitations in the hospital studied and partial social support in patients.